Low-Dose Prophylaxis Versus On-Demand Treatment for Children with Severe Hemophilia A in Indonesia: A Conceptual Model - Khoe, Levina Chandra; Atika, Nur; Pertiwi, Dhia Ticha; Putri, Septiara (UI Scholars Hub, 2026)
Hemophilia A is a rare bleeding disorder caused by a deficiency of clotting factor VIII, leading to recurrent bleeds, joint damage, and disability. Low-dose prophylaxis has been shown to achieve better clinical outcomes than on-demand treatment in reducing bleeding frequency. However, in Indonesia, access and affordability remain key challenges. This study aimed to develop a conceptual model for conducting a health economic evaluation of low-dose prophylaxis treatment for children with severe hemophilia A in Indonesia. This study followed the ISPOR-SMDM Modeling guidelines, outlining two-stage processes: conceptualization of the clinical problem and model development. A systematic literature review was conducted to identify relevant clinical and economic evidence on low-dose prophylaxis and on-demand treatment in pediatric hemophilia A. Indonesian clinical guidelines and expert input from two hematologists were incorporated to contextualize the model. Thirteen studies (three clinical and ten economic evaluations) consistently reported improved outcomes with low-dose prophylaxis. Most models applied health state transitions involving bleeding episodes, joint damage, complications, and death. Based on this review and discussion, the conceptual model was established to support the cost-effectiveness analysis of low-dose prophylaxis. A rigorous conceptual model serves as the key foundational step in developing a valid, health economic model for the Indonesian setting.